Evaluation of the possibility of using an antenna switch with a wideband matching device - Zhanat Manbetova; Assel Yerzhan; Zharkyn Altynov; Zukhra Rakhimzhanova; Gulzada Mussapirova; Pavel Boykachev; Assanali Iskakov; Maria Poleshchuk (Institute of Advanced Engineering and Science, 2026)
This paper investigates the feasibility of integrating a broadband matching device (BMD) with a high-frequency switch into the antenna system of the MIC RL-400M radio relay station, part of the